Evaluation of Patterns and Risk Factors of Substance Abuse among Female Students in Dhaka City, Bangladesh (Community Based Medical Journal, 2026)
Substance abuse among female students in Dhaka city is an escalating public health crisis, severely impacting mental health, academic outcomes, and overall well-being. Despite its growing prevalence, there is a critical research gap concerning the patterns and risk factors specific to this demographic within Bangladesh's unique socio-cultural context. A descriptive, cross-sectional study was conducted among 115 female students admitted in different rehabilitation centers in Dhaka, Bangladesh, between September 2023 and February 2025, to investigate the patterns, predominant risk factors, and consequential impacts of substance abuse. Data was collected via structured interviews using standardized questionnaires. The mean age of participants was 21.88±2.39 years. The most frequently abused substances were amphetamines (69.57%), followed by cannabis (65.22%) and sedatives (63.48%). Academic performance was severely affected, with high rates of declining grades (65.22%), class absenteeism (60.87%), and academic year repetition (42.61%). Prevalent adverse effects included insomnia (79.13%), restlessness (79.13%), euphoria (63.48%), and hostility (61.74%). Depression was a significant risk factor (58.26%; p